The Decade-Long Chinese Methadone Maintenance Therapy Yields Large Population and Economic Benefits for Drug Users in Reducing Harm, HIV and HCV Disease Burden - Zhang, Lei; Zou, Xia; Xu, Yong; Medland, Nick; Deng, Liwei; Liu, Yin; Su, Shu; Ling, Li (Frontiers in Public Health, 2019)
Objectives: We aimed to conduct a comprehensive evaluation of population impact of methadone maintenance treatment (MMT) for its future program planning. Methods: We conducted a literature review of the effects of MMT in China on HIV and HCV disease burden, injecting and sexual behaviours and drug-related harm during 2004-2015. A data synthesis and analysis was conducted to obtain the pool estimates of parameters for a mathematical model which was constructed to evaluate the effectiveness and cost-effectiveness of the program. Results: Based on a review of 125 articles, this study demonstrated that MMT is highly effective in reducing crime-related, high risk sexual and injecting behaviours. The model estimated US1,037m which was invested in MMT from 2004 to 2015 has prevented 19,424 (12,343 -27,257) new HIV infections, 74,898 (59,595-90,972) new HCV infections, 14,924 (8,533-21,315) deaths related to HIV, HCV and drug-related harm, and 317,904 (277,521-359,678) disability-adjusted life years (DALYs). The costs for each prevented HIV infection, HCV infection, death and DALY were 53,401 (38,056-84,035), 13,849 (11,402-17,405), 68,139 (57,675-81,739) and 3,263 (2,884-3,738) respectively. Conclusion: The Chinese MMT program has been effective and cost-effective in reducing injecting, injecting-related risk behaviours and adversities due to HIV/HCV infection and drug-related harm among drug users.